‘Attorneys of the Poor’: the lived experience of general practitioners working in disadvantaged parts of rural Ireland - Catherine Hayes (James Cook University, 2023)
Introduction: The experience of structural violence impacts not only patients but also GPs who deliver their primary care. Farmer (1999) claims that 'sickness due to structural violence results from neither culture nor pure individual will, but historically given and economically driven processes and forces that conspire to constrain individual agency'. I aimed to explore qualitatively the lived experience of GPs in remote rural areas who cared for disadvantaged populations selected from the Haase-Pratschke Deprivation Index (2016). Methods: I visited ten GPs in remote rural areas, did semi-structured interviews, explored the hinterland of their practices and observed the historical geography of their locality. In all cases, interviews were transcribed verbatim. NVivo was used for thematic analysis using Grounded Theory. Findings were framed in the literature around postcolonial geographies, care and societal inequality. Results: Participants were aged from 35 years to 65 years; half were women and half were men. Three main themes emerged: GPs value their lifeworld; they feel at high risk from over-work, inaccessible secondary care for patients and under-acknowledgment of their work; and they experience satisfaction in providing lifelong primary care. They fear that difficulties recruiting younger doctors may terminate the continuity of care that creates a sense of place. Discussion: Rural GPs are linchpins of community for disadvantaged people. But GPs suffer the effects of structural violence and feel alienated from being their personal and professional best. Factors to consider are the roll-out of the Irish government's 2017 healthcare policy, Sláintecare, changes wrought by the COVID-19 pandemic in the Irish healthcare system and poor retention of Irish-trained doctors.